2016
DOI: 10.1002/admi.201600661
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated Metal Oxide Nanosheets as Effective and Applicable Substrates for Atomically Dispersed Metal Nanoparticles with Tailorable Functionalities

Abstract: An effective methodology to stabilize highly dispersed metal nanoparticles is developed by employing the exfoliated 2D metal oxide nanosheets with variable surface structures as substrates. The selection of appropriate crystal structure of titanate nanosheet is very crucial in stabilizing atomically dispersed Pt nanoparticles through the tuning of chemical interaction between Pt and titanate substrate. A theoretical study using density functional theory calculations confirms the significant influence of the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…For the efficient exfoliation of layered inorganic solids, the interlayer distance of the pristine material should be gradually expanded by exchanging small interlayer ions with larger ones, thus reducing the chemical interaction between the host layers . Several layered materials, including layered transition metal oxides (TMOs), layered double hydroxides (LDHs), aluminosilicate clays, layered metal chalcogenides (TMDs), and carbon‐based nanosheets are suitable as host compounds for the intercalation‐based exfoliation method (Figure c) …”
Section: Synthesis and Characteristics Of Exfoliated Inorganic 2d Nanmentioning
confidence: 99%
See 2 more Smart Citations
“…For the efficient exfoliation of layered inorganic solids, the interlayer distance of the pristine material should be gradually expanded by exchanging small interlayer ions with larger ones, thus reducing the chemical interaction between the host layers . Several layered materials, including layered transition metal oxides (TMOs), layered double hydroxides (LDHs), aluminosilicate clays, layered metal chalcogenides (TMDs), and carbon‐based nanosheets are suitable as host compounds for the intercalation‐based exfoliation method (Figure c) …”
Section: Synthesis and Characteristics Of Exfoliated Inorganic 2d Nanmentioning
confidence: 99%
“…The interlayer space of the protonated phase can be further expanded by replacing the protons with specific bulky organic cations, such as tetrabutylammonium (TBA + ). Owing to the weakened interlayer interactions of the host lattice, it can be exfoliated into individual nanosheets with gentle shaking or ultrasonic treatment . Finally, the resulting oxide nanosheets are obtained as a colloidal suspension.…”
Section: Synthesis and Characteristics Of Exfoliated Inorganic 2d Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…Ru K‐edge EXAFS analysis revealed that the ammonolysis was accompanied by local structural transition. As can be observed from Figure 2b, RTO20 exhibits typical Fourier transform (FT) features exhibited by a layered trititanate phase, [ 30 ] clarifying the substitution of Ru ions into the Ti sites of the trititanate lattice. Conversely, RTN20 exhibits an intense FT peak at ≈2.4 Å, which is ascribed to the Ru─Ru bonding pair, as observed in the Ru metal reference.…”
Section: Resultsmentioning
confidence: 99%